2012
DOI: 10.1210/jc.2012-2045
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteocalcin Is Not Associated with Glucose but Is Inversely Associated with Leptin across Generations of Nondiabetic Women

Abstract: Osteocalcin, glucose, and adipokines change with age but in a noncommensurate manner. We infer that the association between osteocalcin and glucose metabolism is minor and age specific in nondiabetic women. Leptin, however, strongly correlated with insulin resistance independently of fat masses, suggesting that obesity, as a metabolic disorder risk factor, affects glucose metabolism, partly through the role of leptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 62 publications
2
34
2
Order By: Relevance
“…In this study, we found negative correlations between leptin and OC, ucOC and OPN levels only in healthy controls. Negative correlations between serum leptin and osteocalcin levels have been reported for non-diabetic women [49]; however, a study in women with type 2 diabetes reported no association [50]. In addition, ucOC, osteocalcin and osteopontin increased in two groups after delivery.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we found negative correlations between leptin and OC, ucOC and OPN levels only in healthy controls. Negative correlations between serum leptin and osteocalcin levels have been reported for non-diabetic women [49]; however, a study in women with type 2 diabetes reported no association [50]. In addition, ucOC, osteocalcin and osteopontin increased in two groups after delivery.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the measurement of total osteocalcin levels instead of the biologically active form ‘uncarboxylated osteocalcin' may appear as a limitation, but there is data confirming a lack of any connection between uncarboxylated osteocalcin and energy metabolism [33,34]. Moreover, carboxylation that depends on vitamin K intake in humans raises more confusion about the optimal activity of osteocalcin [35].…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin-null mice versus wild-type littermates have greater visceral fat, and consequently, present with hyperglycemia and are insulin resistant [3]. In humans, there is conflicting evidence for a relationship between tOC and glucose metabolism with some reports showing no relationship [18, 19], and others showing an inverse relationship between tOC and glucose concentrations [2022]. In contrast, ucOC seems to play a role in pancreatic β-cell proliferation and insulin secretion, as well as improving peripheral insulin sensitivity through the regulation of the adipokine adiponectin [3, 4].…”
Section: Introductionmentioning
confidence: 99%